2011
DOI: 10.3109/10717544.2011.577109
|View full text |Cite
|
Sign up to set email alerts
|

Preparation andin vitro,in vivoevaluations of norfloxacin-loaded solid lipid nanopartices for oral delivery

Abstract: ) Preparation and invitro, invivo evaluations of norfloxacin-loaded solid lipid nanopartices for oral delivery, Drug Delivery, 18:6, 441-450,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 65 publications
(62 reference statements)
2
26
0
Order By: Relevance
“…The rational design of MgNPs comprised the use of PVA as an emulsifier and stabilizing agent. PVA confers remarkably low cytotoxicity and a negative zeta potential to nanoparticles (DeMerlis and Schoneker, 2003;Roy et al 2010;Dong et al 2011). Charges on the nanoparticle surface produce repulsive electrostatic forces that prevent aggregation and help to stabilize the suspension (Min et al 2008).…”
Section: Magnetite-loaded Phbv Nanoparticles (Mgnps)mentioning
confidence: 95%
“…The rational design of MgNPs comprised the use of PVA as an emulsifier and stabilizing agent. PVA confers remarkably low cytotoxicity and a negative zeta potential to nanoparticles (DeMerlis and Schoneker, 2003;Roy et al 2010;Dong et al 2011). Charges on the nanoparticle surface produce repulsive electrostatic forces that prevent aggregation and help to stabilize the suspension (Min et al 2008).…”
Section: Magnetite-loaded Phbv Nanoparticles (Mgnps)mentioning
confidence: 95%
“…Studies of SLNs loaded with lipophilic drugs have yielded promising results. For example, the antibacterial responses of norfloxacin were enhanced when the drug was loaded into SLNs [4]. Moreover, Bose and Michniak observed that SLN encapsulation increased the gastrointestinal absorption of quercetin, as indicated by an increase in the drug bioavailability of 571.4% [5].…”
Section: Introductionmentioning
confidence: 99%
“…26 The lipid phase was prepared by melting stearic acid, lecithin as well as PE at 10°C above the lipid melting point. Meanwhile, the dissolving of tween 80 in deionized water and then heating to the same temperature of the lipid phase was carried out for the preparation of the aqueous phase.…”
Section: Preparation Of Pe-slnsmentioning
confidence: 99%